Rational Choice Institutionalism and the European Neighbourhood Policy - Andrei Cristian Balasan; Andreea Maha (CES Working Papers, 2013)
The aim of this paper is to highlight the main aspects regarding the rational choice theory in neo-institutionalism, and the role the EU Neighbourhood Policy has nowadays. The protagonist of the rational choice theory in the new institutionalism remains homo-economicus. The theory of rational choice institutionalism challenges the perfect rationality of the individual, rather than the principle of rational choice itself. ENP is a framework for consolidating the Union's relations with neighbouring countries and aims therefore intensifying cooperation with them in order to establish a zone of prosperity, good neighbourliness, stability and security.
Keywords: F15; 330; rational choice institutionalism; European Neighbourhood Policy; borders; security; new institutionalism Romania